2013
DOI: 10.1080/09712119.2013.782862
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association of mastitis with allelic variants ofCXCR2gene in Vrindavani cattle

Abstract: The present study was aimed to identify single-nucleotide polymorphic (SNP) sites in coding regions of CXCR2 gene in Vrindavani cattle. A total of 95 animals were screened for CXCR2 gene locus. Single-strand conformation polymorphism (SSCP) analysis revealed polymorphic patterns, and a total of five distinct patterns were observed in the exon 2 of CXCR2 gene. Sequence analysis of different SSCP variants revealed the presence of five novel SNP at A214G, T340C, G344A, C856T and G1027A. No association of mastitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Three SNPs in CXCR2 were reported to be associated with mastitis in Holstein dairy cows and Simmental dairy cows [42]. However, Dige et al [24][25][26][27] investigated the nucleotide variations in CXCR2 coding region in cattle (Vrindavani breed), they reported 5 SNPs with no association to mastitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three SNPs in CXCR2 were reported to be associated with mastitis in Holstein dairy cows and Simmental dairy cows [42]. However, Dige et al [24][25][26][27] investigated the nucleotide variations in CXCR2 coding region in cattle (Vrindavani breed), they reported 5 SNPs with no association to mastitis.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, studies on the association of CXCR2 and mastitis in bovine are limited. CXCR2 has been investigated in Vrindavani cattle by Dige et al, [24,25,26,27]. They reported a lack of association between CXCR2 variations and mastitis.…”
Section: Introductionmentioning
confidence: 99%
“…Another study also reported that miR‐181 was upregulated by TGF‐β (Y. Wang et al 2011). However, the studies of its roles in bone were very few (Dige et al 2013; Su et al 2015). Thus, we explored the relationships between miR‐181d and OPG, an important molecule in bone remodeling.…”
Section: Discussionmentioning
confidence: 99%